Analisis Pendahuluan Pengembangan LKPD Berbasis Etnomatematika pada Materi Segi Empat dan Segitiga - Hidayu Sulisti; Handayani, Lita; Rustanuarsi, Ressy (Jurnal Padegogik, 2025)
LKPD (Ethnomathematics Based Learner Worksheets) has great potential to improve the quality of mathematics learning. However, many LKPDs made by teachers in schools have not been related to the surrounding culture. This article aims to present an initial overview of the development of ethnomathematics-based LKPD. The model used in this research is the Plomp model which consists of 3 stages, namely Prelimenary research (preliminary analysis), Prototyping phase (development or prototyping), and Assessment phase. Due to limited funds and time, this research was carried out only up to the Preliminary Analysis stage. The subjects of this research were students of class VIII of SMP Negeri 05 Sungai Kakap. The first data was obtained from interviews with students, and the second data was obtained from the results of a questionnaire distributed to students. The results of the needs analysis, curriculum analysis, concept analysis, and analysis of the characteristics of students can be concluded that, it is necessary to develop Ethnomathematics-based LKPD on the Quadrangle and Triangle Material, which contains student activities in finding concepts that begin with a problem related and close to the daily lives of students, as well as with language and presentation according to the characteristics of grade VII junior high school students.